Water runoff quality of green roof using natural fibres and recycle waste material - Nurul Shahadahtul Afizah Asman; Salinah Dullah; Abdul Karim Mirasa; Janice Lynn Ayog; Harimi Djamila (UniSE Press, 2017)
This paper investigates the water quality characteristics of green roofs runoff. Parameter included are pH value, total suspended solid (TSS), turbidity and chemical oxygen demand. The data were collected from nine different test bed under simulated rainfall. Three types of recycled waste are selected for each test bed which is rubber crumbs, palm oil shell, and polyfoam. Natural fibres as the filter layer in green roofs are placed on top of the drainage layer. Natural fibres chosen are coconut fibre, palm oil fibre and sugarcanes fibres. Another test bed with waterproofing layer as a control. From the results obtained shows that rubber crumbs are suitable as a drainage layer and, palm oil fibre or coconut fibre are suitable for filter layer of green roofs. A green roofs should be able to neutralised acid rain by stabilizing the pH, reduce the turbidity, total suspended solid (TSS) and chemical oxygen demand (COD).